2019
DOI: 10.7554/elife.44934
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-driven regulation of voltage-sensing domains in BK channels

Abstract: Allosteric interactions between the voltage-sensing domain (VSD), the Ca2+-binding sites, and the pore domain govern the mammalian Ca2+- and voltage-activated K+ (BK) channel opening. However, the functional relevance of the crosstalk between the Ca2+- and voltage-sensing mechanisms on BK channel gating is still debated. We examined the energetic interaction between Ca2+ binding and VSD activation by investigating the effects of internal Ca2+ on BK channel gating currents. Our results indicate that Ca2+ sensor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…S1 ). Gating charges were calculated by integrating the early gating currents elicited by the voltage steps using a previously reported procedure that excludes charge displacements associated with channel opening ( 21 , 38 40 ) ( SI Appendix, Materials and Methods ). Since the half-activation voltages ( ) of mutants R207Q and R210Q were largely leftward shifted ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S1 ). Gating charges were calculated by integrating the early gating currents elicited by the voltage steps using a previously reported procedure that excludes charge displacements associated with channel opening ( 21 , 38 40 ) ( SI Appendix, Materials and Methods ). Since the half-activation voltages ( ) of mutants R207Q and R210Q were largely leftward shifted ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of L390P mutations, our observations that RCK1 Ca 2+ sites acting alone make a greater contribution to Ca 2+ activation than Ca 2+ bowl sites acting alone, and that the sum of ΔV1/2 0→100 µM Ca for RCK1 Ca 2+ sites alone and Ca 2+ bowl sites alone can exceed ΔV1/2 0→100 µM Ca for WT channels has been described previously (47,48). Also observed by others have been equal contributions of the RCK1 Ca 2+ site and Ca 2+ bowl to left shifts in V1/2 (7,8,49), and equal contributions of these sites to decreasing the free energy necessary to activate voltage sensors (43). The reason for the apparent differences in the relative contributions from the two types of Ca 2+ sites is not known.…”
Section: Disruption Of the αB Helix Decreases High Affinity Ca 2+ Senmentioning
confidence: 66%
“…The αB Helix/VSD Interface is Required for Effective Voltage and Ca 2+ Activation of BK Channels. Functional studies have suggested that voltage and Ca 2+ sensors of BK channels interact, as summarized in the Introduction (6,13,15,28,30,40,41,43,44), and that the AC (N-lobe) region of the CTD is involved (25,51). Structural studies have identified a potential structural pathway to couple Ca 2+ sensors in the CTD with voltage sensors in the TMD (16,17,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While direct assessment of allosteric coupling between the VSD and CSD (parameter E) has historically been challenging, it was recently hypothesized that VSD-CSD coupling may have a substantial impact on voltage-dependent activation (Lorenzo-Ceballos et al, 2019;Hite et al, 2017). Consistent with this idea, although both Fit A and Fit B describe G-V-Ca 2+ relations similarly well at 0 µM NS11021 (Table 1), changing L 0 in Fit A better accounts for the observed effects of NS11021 at higher drug concentrations and contains an 18-fold greater value for parameter E than Fit B ( Fig.…”
Section: Limitations Of the Proposed Mechanismmentioning
confidence: 99%